2002
DOI: 10.1302/0301-620x.84b4.0840497
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of anabolic steroids, vitamin D and calcium on muscle mass, bone mineral density and clinical function after a hip fracture

Abstract: A total of 63 women who had an operation for a fracture of the hip was randomly allocated to one year of treatment either with anabolic steroids, vitamin D and calcium (anabolic group) or with calcium only (control group). The thigh muscle volume was measured by quantitative CT. The bone mineral density of the hip, femur and tibia was assessed by quantitative CT and dual-energy x-ray absorptiometry and of the heel by quantitative ultrasound. Quantitative CT showed that the anabolic group did not lose muscle v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…Activities of daily life (ADL) functions were preserved in patients given the protein-rich supplementation, whereas positive effects were registered for lean body mass, ADL and quality of life in those who received the combined therapy. Similar findings were reported by Hedströ m et al [12], who randomly assigned half of 63 patients to nandrolone treatment every third week for one year, resulting in preserved lean body mass and bone density together with improved gait speed and Harris hip score.…”
Section: Hormonal and Combined Anabolic Intervention Approachessupporting
confidence: 85%
“…Activities of daily life (ADL) functions were preserved in patients given the protein-rich supplementation, whereas positive effects were registered for lean body mass, ADL and quality of life in those who received the combined therapy. Similar findings were reported by Hedströ m et al [12], who randomly assigned half of 63 patients to nandrolone treatment every third week for one year, resulting in preserved lean body mass and bone density together with improved gait speed and Harris hip score.…”
Section: Hormonal and Combined Anabolic Intervention Approachessupporting
confidence: 85%
“…95 Low-dose AASs have also been shown to improve functional outcome in elderly women after hip fracture, exhibiting a beneficial effect on muscle mass and bone mineral density. 39…”
Section: Therapeutic Usesmentioning
confidence: 99%
“…In one 4-week pilot study, there were no positive effects found on ADL (Sloan et al 1992, Table). A 1-year study with nandrolone decanoate together with vitamin D and calcium resulted in retained muscle volume and a better function postoperatively (Hedström et al 2002) (Table). This was also found by Tidermark et al (2004) who reported a positive effect on lean body mass, ADL and quality of life after nandrolone decanoate treatment in combination with nutritional supplementation for 6 months after a hip fracture (Table).…”
Section: Pharmacological Intervention Trialsmentioning
confidence: 99%